2013
DOI: 10.1074/jbc.m112.424366
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Fibronectin Signaling Induces Matrix Metalloproteases and Cyclooxygenase-2 (COX-2) in Amnion Cells and Preterm Birth in Mice

Abstract: Background:The function of fetal fibronectin (fFN) in the pathogenesis of preterm labor is not known. Results: fFN activates MMP-1, MMP-9, and COX-2 in mesenchymal cells and causes preterm labor in mice. Conclusion: fFN is biologically active and plays a significant role in the pathogenesis of preterm labor. Significance: Signaling of fFN in fetal membranes is important in the pathophysiology of premature preterm rupture of the membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Further, thrombin-induced increases in these TLR4 target genes were not mitigated by endotoxin removal, and endotoxin-free recombinant thrombin also increased MMP1 and COX2. Interestingly, we found that thrombin also stimulated release of fibronectin from its cellbound fibrillar form to its soluble form, which is known to activate TLR4 (23). Thrombin-induced release of fibronectin occurred even in epithelial cells with nonfunctioning TLR4 complexes, indicating that thrombin-induced activation of MMP1 was not required.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Further, thrombin-induced increases in these TLR4 target genes were not mitigated by endotoxin removal, and endotoxin-free recombinant thrombin also increased MMP1 and COX2. Interestingly, we found that thrombin also stimulated release of fibronectin from its cellbound fibrillar form to its soluble form, which is known to activate TLR4 (23). Thrombin-induced release of fibronectin occurred even in epithelial cells with nonfunctioning TLR4 complexes, indicating that thrombin-induced activation of MMP1 was not required.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, thrombin treatment (4 units/ml (36 nM) ϫ 48 h) dramatically increased soluble fibronectin in conditioned media from both amnion mesenchymal cells (TLR4-responsive) and epithelial cells which do not express functional TLR4 (Fig. 8B) (23). Further, in contrast with mesenchymal cells, thrombin-induced release of fibronectin was not accompanied by increased expression of COX2 and MMP1 in epithelial cells (data not shown).…”
Section: Up-regulation Of Mmp9 Mrna Is Mediated Via Par-1-tomentioning
confidence: 83%
See 2 more Smart Citations
“…9,17,18 The EDA domain of fibronectin can activate TLR4 signaling as either the individual domain, proteolytic fragment or in the context of the intact molecule. 19,20 Being responsible for matrix synthesis, assembly, and turnover, stromal fibroblasts are in constant dialogue with the fibronectin matrix in its polymerized and fragmented forms. Changes in tissue mechanical forces have been shown to cause the structurally labile fibronectin type III (FnIII) domains to unfold, revealing otherwise hidden bioactive sites.…”
mentioning
confidence: 99%